Psammobatis rutrum, spade sandskate - Pollom, R. (2020)
The Spade Sandskate (Psammobatis rutrum) is a small (to 32 cm total length) skate that occurs in the Southwest Atlantic from Rio de Janeiro, Brazil to the San Matías Gulf, northern Chubut, Argentina. It inhabits the continental shelf at depths of 31–150 m. It is captured in demersal trawl fisheries, which are intense in parts of its range. There are no estimates of population trend for this species, but it is still caught commonly in fisheries despite a long history of fishing pressure, and therefore the population size is suspected to be stable. Its small size indicates that it likely has an early age-at-maturity and a fast growth rate and thus some ability to withstand fishing pressure. Therefore, the Spade Sandskate is assessed as Least Concern.